First report of the genus Colastomion Baker, 1917 (Hymenoptera: Braconidae) from the Indian mainland and Andaman Islands with description of two new species - Gupta, Ankita (Zootaxa, 2026)
The relatively uncommon and small genus Colastomion Baker, 1917 is recorded for the first time from the Indian mainland as well as from the Andaman group of islands. Two new species, Colastomion indominutus Gupta, sp. nov. and Colastomion indosubequalis Gupta, sp. nov., are described and illustrated. Both the newly described species are compared with the other similar appearing Colastomion species known from the Oriental region.